Episodic Migration of Oaks to Iceland: Evidence for a North Atlantic "Land Bridge"in the latest Miocene - Thomas Denk (The Swedish Museum of Natural History); Fridgeir Grimsson (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Reinhard Zetter (Department of Palaeontology, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna) (American Journal of Botany, 2010)
The abstract is available here: https://uscholar.univie.ac.at/o:243775 The abstract is available here: https://uscholar.univie.ac.at/o:243775